IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS CERITA RAKYAT DALAM PEMBELAJARAN IPAS UNTUK MENGENALKAN SEJARAH LOKAL KEPADA SISWA SEKOLAH DASAR - Alia Siti Masitoh; Eka Salvia Putri; M.Fikri Maulana Firdaus; Rikul Rosana; Puput Komalasari; Dine Trio Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of a folk‐based learning model in Natural and Social Sciences (IPAS) instruction as an effort to introduce local history to elementary school students. The background of this research lies in students’ low interest in local historical knowledge due to instructional practices that remain verbal, less contextual, and minimally integrated with cultural media. The folk‐based learning model was selected because it connects factual understanding with cultural values, local figures, and historical events embedded in students’ daily lives. This research employed a qualitative approach with a classroom action research design conducted in two cycles. The participants were fourth‐grade students from an elementary school in Lebak Regency. Data were collected through observation, interviews, documentation, and learning outcome analysis. The findings indicate that the use of local folk narratives significantly increased students’ enthusiasm, comprehension of IPAS concepts, and awareness of local historical identity. Folk stories such as legends, place origins, and local heroes created meaningful learning experiences by presenting narrative elements, imagination, and cultural wisdom. The study concludes that the folk‐based learning model is effective in IPAS instruction and contributes to strengthening students’ cultural identity and appreciation of local heritage.